EFEKTIVITAS MODEL PROBLEM BASED LEARNING (PBL) BERBANTU MEDIA PADLET UNTUK MENDUKUNG KEMAMPUAN PEMECAHAN MASALAH SISWA SMP - Ilmi, Maulidinatul; Suesthi Rahayuningsih; Feriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students' mathematical problem-solving ability at MTs Manba'ul Ulum was still relatively low, indicated by the difficulty most students had in responding to questions related to the information given in the problems, as well as their tendency to rely on friends' help instead of independently writing down a solution plan. This study aimed to determine the effectiveness of the Problem Based Learning (PBL) model assisted by Padlet media in supporting junior high school students' problem-solving ability, reviewed from teacher activity, student activity, and students' problem-solving ability, each of which was required to be at least in the good category. This study used a quantitative method with a one-shot case study design. The population of this study was seventh-grade students of MTs Manba'ul Ulum Gondang, with the sample determined using a purposive sampling technique, namely class VII-C consisting of 20 students. Data collection techniques used observation sheets to observe teacher and student activities, as well as a test to measure students' problem-solving ability. The results showed that teacher activity obtained a percentage of 92.59% in the very good category, student activity obtained a percentage of 86.50% in the very good category, and the problem-solving ability test results showed that 16 out of 20 students obtained scores in the minimum good category, with a classical percentage of 80%. Thus, it could be concluded that the Problem Based Learning (PBL) model assisted by Padlet media was effective in supporting students' problem-solving ability